Innovation in Media/Journalism Education and Research in Ghana - Gyambrah, Martin; Hanson, Priscilla (Journal of Communications, Media & Society, 2016)
Rapid changes in the world today places a demand on journalism practice to take a new outlook that is underpinned by an innovative approach in its education and research. This study examined innovation in journalism education and research in Ghana. Qualitative approach to data collection and research was employed. Sample was selected using purposive and convenience sampling techniques. Sample consisted of journalism scholars and practitioners in tertiary educational institutions in Greater Accra region, Ghana. Data collected from the interview was analysed using thematic analysis. Key findings point to a disagreement in views regarding the gap between what is taught in the classroom and what is practised on the field. Journalism instructors were of the view that no such gap exists whereas the practitioners were of the opinion that a gap does exist. It is recommended that curriculum enrichment, teaching online journalism, organizing workshops and seminars for students, involving practitioners in curriculum development be promoted.
Research Article
Keywords: Innovation, Media, Journalism, Education, Research, Ghana